Las unidades espaciales asociadas a la religiosidad chilota: Evolución de las entidades pobladas - Sahady Villanueva, Antonio; Gallardo Gastelo, Felipe Eduardo; Bravo Sánchez, José; Ibáñez Browne, María de los Ángeles (Revista de Urbanismo, 2007)
In the foundational history of the different Chiloé towns it is possible to notice that the church -as much architectonic as symbolic object- constituted the center from which the development of the different urban settlements existing in the archipelago generated. However, today the effects of globalization and specially the urban development are attempting to this culture, invading cultural spaces that it involucrated in the development of religious expressions that surpass the limits of the church as property.